The Influence of Work Environment, Workload and Work Motivation on Employee Performance at PT. Mahatma Agro - Cahyaningrat, Wahyu; Kusumaningtyas, Dian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The purpose of this study was to determine and analyze whether the work environment, workload, and work motivation affect employee performance both partially and simultaneously. Design/Methode/Approach: The type of research used in this research is quantitative research. The data collection technique used was distributing questionnaires in the form of Google Forms to all samples totaling 47 respondents. The analysis technique used is a multiple linear regression analysis technique with the help of Statistical Product and Service Solution (SPSS) version 24.00 software. Research Finding: The results of this study indicate that the work environment (X1) and Workload (X2) partially and significantly affect the performance of employees of PT Mahatma Agro (Y). Work motivation (X3) partially has no significant effect on the performance of PT Mahatma Agro employees. The results of the study simultaneously show that the work environment, workload, and work motivation have a significant effect on the performance of PT Mahatma Agro employees. Theoretical contribution/Originality: This research can contribute and add to the literature by showing how work environment, workload, and work motivation affect the performance of PT Mahatma Agro employees. This shows how important it is to think about these three factors to get a better understanding of the work environment, workload, and motivation on employee performance. Practitioner/Policy implication: The results of this study can provide insight and illustration for companies that are creating a positive and supportive work environment, providing a balanced workload, and providing appropriate and effective work motivation programs are the keys to achieving company goals and improving employee performance. Research limitation: The limitation of this study is that it only focuses on three variables (work environment, workload, and work motivation) without considering other variables that might affect employee performance. The second limitation lies in the use of research methods with questionnaires that have the potential for respondent bias such as dishonest answers not by the actual situation, and some employees do not fill out or collect questionnaire answers.